A CASE STUDY ON DOWN SYNDROME USING PEDIGREE ANALYSIS - et. al, Gowri.P (International Journal of Advanced Science and Technology, 2019)
A Case study on “Down syndrome using Pedigree analysis” discuss about the genetics using Linear Algebra. Down syndrome is a genetic disease that arise when the abnormal cell division will end in extra full or partial copy of chromosome 21. In this paper, we have employed the concepts from Linear Algebra to predict the genotypic distribution of the Down syndrome disease with autosomal inheritance. Autosomal inheritance is a pattern of inheritance in which the transfer of characters depends on the presence of the alleles on the autosomes. We have used the pedigree analysis by which we have calculated the highest power of the matrix of the nth generation by which we can predict the individual’s prone to disease.